2018
DOI: 10.1097/brs.0000000000002545
|View full text |Cite
|
Sign up to set email alerts
|

Tidemark Avulsions are a Predominant Form of Endplate Irregularity

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Previous work has focused mainly on the bony vertebral endplates, in cadaveric or animal tissues, and on MRI (Adams and Dolan, 2012; Adams et al, 2000; Berg‐Johansen et al, 2018b; Berg‐Johansen et al, 2018a; Feng et al, 2018; Fields et al, 2014; Rade et al, 2018; Wang et al, 2012). Some defects in cadaveric tissues may be artefactual, and defects in young animal tissues may not accurately represent those in ex vivo tissues obtained from living humans, as identified in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has focused mainly on the bony vertebral endplates, in cadaveric or animal tissues, and on MRI (Adams and Dolan, 2012; Adams et al, 2000; Berg‐Johansen et al, 2018b; Berg‐Johansen et al, 2018a; Feng et al, 2018; Fields et al, 2014; Rade et al, 2018; Wang et al, 2012). Some defects in cadaveric tissues may be artefactual, and defects in young animal tissues may not accurately represent those in ex vivo tissues obtained from living humans, as identified in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The endplate may be most relevant clinically, considering that endplate defects are associated with pathologic disc innervation (Fields et al, 2014), and a history of severe back pain (Lama et al, 2018). Cadaver and histology studies show that tidemark avulsions, CEP ruptures, and bony endplate lesions are the predominant form of endplate irregularity (Berg‐Johansen et al, 2018b; Berg‐Johansen et al, 2018a; Fields et al, 2014; Kakitsubata et al, 2002; Tanaka et al, 1993; Wang et al, 2012), and that fragmentation of the CEP is associated with back pain and sciatica (Lama et al, 2014). However, the structural features of damaged CEPs have not been well characterized, and this hinders our understanding of the etiology of disc degeneration and pain.…”
Section: Introductionmentioning
confidence: 99%
“…Another informative correlation determined from the present study was between the micromechanical AFM measurements ( E ind CEP, AF, AF‐EP) and whole motion segment macro‐mechanical properties (toe and linear modulus). Other groups have previously evaluated NP (Iatridis et al, 1996), AF (Iatridis et al, 1999), endplate (Berg‐johansen et al, 2018), and motion segment (Cortes et al, 2014; Pollintine et al, 2010) mechanics in isolated studies. To the best of our knowledge, this is the first study to report a relationship between micro and macroscale mechanic perturbations in IVD tissues with degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Forms of damage have been described as fractures (Fig. 1E), erosions, Schmorl’s nodes, avulsions, calcification, and rim degeneration [33, 82, 83]. Depending on the imaging technique, the prevalence varies between nodes and erosions being most prevalent (22% and 14%) (Fig.…”
Section: Endplate Pathology and Relations To Disc Degenerationmentioning
confidence: 99%
“…1C) to avulsions and rim degeneration (35% and 50%). In a recent histopathology study, Berg-Johansen et al reported that ninety percent of avulsions were subclassified as “tidemark avulsions,” a form of endplate irregularity wherein the outer annulus separates from the vertebra at the enthesis tidemark [83] (Fig. 1B).…”
Section: Endplate Pathology and Relations To Disc Degenerationmentioning
confidence: 99%